Development of Respiration Measurement Methods Using Wearable Gyroscope and Acceleration Sensors - Ikarashi, Akira (Sensors and Materials, 2025)
To diagnose respiratory diseases, it is essential to quantify the respiratory rate and respiratory movements. Moreover, the assessment of respiratory movements is a valuable tool for the evaluation of autonomic nervous system function, including the assessment of stress load. The present techniques for measuring respiration encompass the thermistor method, inductance method, and electrical impedance method. However, the thermistor and inductance methods present certain difficulties in terms of sensor attachment, and they place a significant burden on the subject. Furthermore, the electrical impedance method is susceptible to the effects of body movements and other factors. Conversely, considerable research is being conducted on the use of IoT in the development of wearable healthcare devices, which employ gyroscope and acceleration sensors. In this study, we attempted to measure respiratory movements by attaching a 6-axis sensor (comprising a 3-axis gyroscope sensor and a 3-axis acceleration sensor) to the chest. As a result, it was demonstrated that respiratory movements can be accurately measured even when the 6-axis sensor is attached to clothing.